Tradisi Wisuda Secara Adat di Masyarakat Lekuk 50 Tumbi Lempur, Kabupaten Kerinci, Jambi - Yolla Ramadani; Astrid Qommaneeci (Universitas Andalas, 2020)
This article is the result of research conducted with the aim to determine the effect of traditional graduation traditions on increasing community motivation in continuing education to tertiary institutions. The Traditional Graduation Tradition is the awarding of a degree given by the Indigenous Institution of 50 Tumbi Lempur Indigenous Peoples to local sons and daughters who have completed a Bachelor, Master, Doctoral degree, or Professor. The awarding of this title is carried out royally every year on the second of Shawwal. This research uses a descriptive qualitative method where data is collected by observation, interview, and documentation study. The results showed that this tradition is still carried out by the community until now because this tradition has grown a very large motivation for every child and parent to be able to continue their education up to college. This motivation arises both from internal and external from the community. One of the external motivations arises because of the pride felt by each family when their children are given a title in front of the entire community of Lekuk 50 Tumbi Lempur. While internal motivation arises, one of which is due to the desire of children to achieve achievements and reach goals so that they can boast of the family.